Intercropping of mukhikachu and papaya with pineapple - Khan, M A H; Rahman, M M; Sultana, N (SAARC Journal of Agriculture, 2023)
The experiment was carried out at the farmers’ field condition under On-Farm Research Division, Bangladesh Agricultural Research Institute, Tangail during 2016-18 and 2018-20 to find out suitable intercropping system for increasing crop productivity and profitability of pineapple + mukhikachu + papaya intercropping system. The treatments were viz. T1 = Pineapple (100%) + Mukhikachu (40%), T2 = Pineapple (100%) + Papaya (66%) and T3 = Pineapple (100%) + Papaya (66%) + Mukhikachu (40%), T4 = Pineapple (100%), T5 = Mukhikachu (100%), T6 = Papaya (100%). Pineapple (Honey queen), Mukhikachu (Bilashi) and Papaya (Shahi) were used as test materials. The experiment was laid out in a randomized complete block design with six dispersed replications. Pineapple was the main crop, mukhikachu and papaya were intercrop in the study. Among three intercropped treatments, pineapple (100%) + papaya (66%) + mukhikachu (40%) within two paired rows of pineapple (T3) showed higher equivalent yield of pineapple, mukhikachu and papaya 70.37, 46.91 and 58.64 tha-1, respectively which provided yield advantages of 57, 138 and 92 % over their respective sole crops. The highest land equivalent ratio (1.83), gross return (Tk 7,03,700 ha-1) and benefit cost ratio (2.04) were achieved in this treatment (T3) compared to other cropping systems. The higher values of all competition functions were also exhibited in Pineapple (100%) + Papaya (66%) + Mukhikachu (40%) intercropping system. Thus, it could be stated that papaya (66%) and mukhikachu (40%) in between two paired rows of pineapple was the most productive and profitable intercropping system for the farmers of Madhupur Tract (AEZ-28). SAARC J. Agric., 21(1): 25-38 (2023)